Microscopic pore-throat utilization characteristics of advanced fracturing-flooding water injection in tight oil reservoirs - Shi, Jianchao; Zhang, Qiuyue; Liu, Jian; Zhang, Meng; Shi, Luming; Wang, Di (Frontiers in Earth Science, 2026)
Advanced fracturing–flooding water injection (AFWI) technology provides an effective approach to overcoming the limitations of conventional waterflooding in tight oil reservoirs, particularly the issues of low sweep efficiency and poor recovery. Nevertheless, the mechanisms governing pore–throat utilization during this process remain insufficiently understood. In this study, a combination of nuclear magnetic resonance (NMR) experiments and finite element (FE) simulations was employed to investigate the microscopic displacement behavior of tight cores under different scales of advanced fracturing–flooding water injection. The results show that AFWI increased the initial displacement pressure differential from 6.34 MPa (pre-injection volume (Vpre) = 0) to 7.56 MPa (Vpre = 0.3) and 8.45 MPa (Vpre = 0.6), advanced the waterflood front by 1.5 cm (Vpre = 0.3) and 2.6 cm (Vpre = 0.6), and raised ultimate oil recovery from 35.5% to 40.5% and 43.5%. Low-field nuclear magnetic resonance (LF-NMR) spectra were calibrated to pore radius via mercury intrusion, showing enhanced recovery in medium–small throats under larger Vpre. Microscopic simulations revealed that increasing Vpre intensifies the pressure gradient between injection and production ends, activating flow pathways within smaller pores and improving overall pore–throat utilization. The integrated experimental and numerical findings advance understanding of pore-scale fluid dynamics in tight reservoirs and provide theoretical guidance for optimizing AFWI strategies.